Funding Maine’s Mortgage Market (Or, Who Sets Mortgage Rates, Anyway?) - Pinkham, Chris (Maine Policy Review, 1999)
Some have argued that the state of Maine sits in a far away corner of the nation’s transportation system, and others feel that map makers have slighted our state in terms of its northern and eastern boundaries to accommodate large, flat maps of the country. Maine’s mortgage market may well be the opposite situation as both rates and a bank’s funding sources are not uniquely positioned as transportation or cartography may be. Rather, the mortgage business is part of a complex web of international markets that, for all practical purposes, has taken rate-setting away from Maine lenders and provided Maine consumers with choice rates